Costing Adaptation through Local Institutions : Village Survey Results - Ethiopia - World Bank (Washington, DC, 2017)
In Ethiopia, village surveys were conducted in six villages and two expert workshops were organized to discuss the organization of the study and to evaluate the draft results. Based on household surveys, focus group discussions, and institutional stakeholder interviews, we assessed household vulnerability, analyzed the strategies households adopt to reduce the hazards faced, and evaluated the assistance households receive from institutions. Vulnerability profiles were formulated, which show that household vulnerability differs substantially among and within villages. The size and diversity of income and the ability to flexibly decide on alternative measures to mitigate the adverse climate effects, which depends on, for example, level of education and dependency ratio, have effects on the adaptation options households adopt and the type of institutional assistance they receive. This report presents the results of the World Bank-funded project on Costing Adaptation through Local Institutions (CALI). The objectives of the CALI-project are: (1) to identify the costs of adaptation through local institutions, and (2) to investigate the institutions that support households in adapting to climate variability, the efforts and costs required to realize the adaptation options, and how they facilitate adaptation to climate variability. The study has been carried out in Ethiopia, Mali, and Yemen. This report discusses the results for Ethiopia.